Challenges encountered by Malaysian prosecutors in human trafficking - Ab Hamid, Zuraini; Ab Aziz, Norjihan; Mohamad Amin, Noor Shuhadawati (AESS Publications, 2018)
Anti-Trafficking in Persons and Smuggling of Migrants Act 2007 is the federal antitrafficking and anti-smuggling legislation in Malaysia. Ten years after its enactment, fewer cases on human trafﬁcking were identified. Statistics showed that the number of the victim saved and perpetrators prosecuted before the courts have reduced, although some commentators suggested that the original estimates of the cases are higher due to recent modern approaches in slavery. Some scholars claimed that the act by its nature is already a comprehensive set of laws to prevent the crime since its first introduction compared to other Tier 1 countries in Trafficking in Persons (TIP) report such as Australia which has gradually enhanced its legislation. However, the comprehensiveness of the act does not guarantee the prevention of human trafficking due to the ineffectiveness of prosecution officers in prosecuting the perpetrators, thus denying the rights of the victims to be protected as reported in TIP reports from 2010 until 2017. This is a qualitative and legal studies adopting doctrinal and legal research approaches. This paper analyzed the prosecution of human trafficking cases in Malaysia. The findings revealed the obstacles faced by the prosecution officers in carrying their duties against the perpetrators, contributed by enacted legislation, nongovernmental organizations, judiciary officers, and enforcement bodies.